Clinical features of Rheumatoid Purpura in adults - El Arabi Yasmina; Hali F; Marnissi F; Chiheb S (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2022)
Introduction: Rheumatoid purpura is a systemic vasculitis of small vessels that is more common in children than in adults. The aim of our study was to revise the characteristics of rheumatoid purpura in adults. Methods: We conducted a retrospective descriptive and analytical study [June 2016 - June 2021], including all the patients hospitalized in the dermatology department of Ibn Rochd University Hospital for rheumatoid purpura. We first described the characteristics of adult patients aged over 18 years old, and then we compared them to those of the children (<18 years old) to determine the clinical features in adults.  Results: A total of 18 adults (15 women/3 Men) and 9 children were collected. Adults had a mean age of 48 years [27-66 years]. Vascular purpura was constant, complicated by necrosis in 12 patients, bullae in 6 patients, and ulceration in 2 patients. Joint involvement was present in 16 patients. Ten patients presented digestive signs: epigastralgia (n= 4), abdominal pain (n= 8), and rectal bleeding (n= 2). Cutaneous biopsy showed leukocytoclastic vasculitis in all patients with IgA and C3 deposition in 13 patients. Renal involvement was present in 6 patients. After comparison with the children group, the particularities in adults were the absence of previous drug intake (p= 0.009), absence of pruritus (p= 0.009), presence of bullae (p= 0.05), presence of severe digestive involvement (p= 0.033), joint involvement (p= 0.003), and presence of anemia (p= 0.017).  Conclusion: Rheumatoid purpura in adults is characterized by its severe clinical features.